Disrupting Whiteness as Higher Education: Towards a Systemic Decoloniality - Knaus, Christopher (International Journal of Educational Development in Africa)
This creative conceptual paper expands traditionalised academic approaches through integrated narratives, plays, lyrics, and poetry as decolonial method. Based in first person narratives, informal interviews, artistic expression, and music-integration, the author clarifies tensions in decolonial strategy, including moving beyond racial representation to acknowledge and respond to racialised poverty, racism built into the fabric of higher education, and an overarching denial of racial disparities. The paper begins with a discussion of the student-created and produced play, The Fall, which brings the #RhodesMustFall movement onto the stage. Integrating student discussions and reactions to the play, the paper echoes themes from The Fall, suggesting that strategies which interrupt coloniality, while necessary, are insufficient to transform from formal education’s capitalistic and exploitative foundation. In centring USA and South African writers, the paper highlights that the purpose of education remains a White supremacist vision and that to move from such anti-Black infrastructures, transformation must align directly with ongoing, student-led decolonial approaches. The paper then parallels higher education protests to the context of the 2010 World Cup’s artistic exploitation of South Africa, warning of the power of appropriation, especially on a global stage. The paper concludes with the affirmation that creative, artistic, and Black-centric voices must be fostered and integrated into decolonial strategies to transform the global Whiteness of higher education.